2003
DOI: 10.1086/375595
|View full text |Cite
|
Sign up to set email alerts
|

Human Illness Associated with Use of Veterinary Vaccines

Abstract: Veterinary vaccines are being used with increasing frequency in the United States to protect the health of animals. However, humans may be inadvertently exposed to these products by means of unintentional inoculation or other routes of exposure. The potential for both exposure and for adverse consequences secondary to exposure to veterinary vaccines may be growing. With the exception of brucellosis vaccines, there have been few reports of suspected or confirmed adverse events in humans associated with the use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(24 citation statements)
references
References 25 publications
0
24
0
Order By: Relevance
“…There are documented cases showing the pathogenic nature of strains Rev. 1 and S19 in humans [14]. Thus, for the effective monitoring of both brucellosis control programs and human disease it is important to have reliable tests to differentiate vaccine and field strains.…”
Section: Introductionmentioning
confidence: 99%
“…There are documented cases showing the pathogenic nature of strains Rev. 1 and S19 in humans [14]. Thus, for the effective monitoring of both brucellosis control programs and human disease it is important to have reliable tests to differentiate vaccine and field strains.…”
Section: Introductionmentioning
confidence: 99%
“…Commercially available vaccine strains used for brucellosis eradication in cattle have been tested in wildlife species (Davis and Elzer, 2002), but results from elk vaccination trials have shown that efficacy is reduced in comparison to cattle. Additional vaccination-related problems include interference with diagnosis (Schurig et al, 2002), resistance to antibiotics, and potential virulence for animals and humans (Berkelman, 2003; Ashford et al, 2004). The B. abortus strain 19 (S19) appeared to be safe in adult elk but has been shown to reduce abortion rates only by 30% (Thorne et al, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…No additional details are available about this patient but an avian source of exposure seems plausible. A number of reports provide evidence to suggest that many human infections are the result of contact with infected or vaccinated pets (Gueirard et al 1995;Dworkin et al 1999;Foley et al 2002;Berkelman 2003;Rath et al 2008;Register et al 2012;Brady et al 2014;Garcia-de-la-Fuente et al 2015). An example of typing data in support of this concept, acquired here and from a prior study (Register et al 2012), is the finding that of 14 B. bronchiseptica isolates known to be ST27/RT4, six were cultured from humans, seven from dogs or cats and one from a pig.…”
Section: Discussionmentioning
confidence: 99%